2008
DOI: 10.1002/dvdy.21552
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four Engrailed genes in the Japanese lamprey, Lethenteron japonicum

Abstract: We have isolated four homologs of Engrailed genes from the Japanese lamprey, Lethenteron japonicum, an agnathan that occupies a critical phylogenic position between cephalochordates and gnathostomes. We named these four genes LjEngrailedA, LjEngrailedB, LjEngrailedC, and LjEngrailedD. LjEngrailedA, LjEngrailedB, and LjEngrailedD share a major expression domain in the presumptive midbrain-hindbrain boundary region of the central nervous system, although their levels and timing of expression differed. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…3.12 ; Hatta et al 1990 ;Holland et al 1993 ;Matsuura et al 2008 ;reviewed in Holland et al 2008b ;Sambasivan et al 2011 ). Moreover, one of the four lamprey Engrailed genes is expressed in the ectoderm of the pharyngeal arches (Matsuura et al 2008 ), similar to expression of amphioxus Engrailed in a stripe in the ectoderm ventral to the fi rst somite .…”
Section: Evolution Of Head Segmentation In Chordatesmentioning
confidence: 88%
See 1 more Smart Citation
“…3.12 ; Hatta et al 1990 ;Holland et al 1993 ;Matsuura et al 2008 ;reviewed in Holland et al 2008b ;Sambasivan et al 2011 ). Moreover, one of the four lamprey Engrailed genes is expressed in the ectoderm of the pharyngeal arches (Matsuura et al 2008 ), similar to expression of amphioxus Engrailed in a stripe in the ectoderm ventral to the fi rst somite .…”
Section: Evolution Of Head Segmentation In Chordatesmentioning
confidence: 88%
“…For example, Engrailed is expressed in the posterior wall of the anterior somites in amphioxus embryos; in the velar and upper lip muscles of the lamprey, which develop from the mandibular head cavity; in the mandibular arch in the shark; and in the jaw muscles of gnathostomes ( Fig. 3.12 ; Hatta et al 1990 ;Holland et al 1993 ;Matsuura et al 2008 ;reviewed in Holland et al 2008b ;Sambasivan et al 2011 ). Moreover, one of the four lamprey Engrailed genes is expressed in the ectoderm of the pharyngeal arches (Matsuura et al 2008 ), similar to expression of amphioxus Engrailed in a stripe in the ectoderm ventral to the fi rst somite .…”
Section: Evolution Of Head Segmentation In Chordatesmentioning
confidence: 96%
“…Recent studies showed that the lamprey harbours four En genes that were multiplied independently in the agnathan lineage and may have assumed novel roles (Matsuura et al, 2008). Remarkably, one of these genes is initially expressed in the centre of the somite before adopting a more widespread pattern (Hammond et al, 2009).…”
Section: A Possible Scenario For the Evolution Of Vertebrate 3d-mobilitymentioning
confidence: 99%
“…Yet distinct dorsal and ventral rami of the spinal nerves that can trigger localised dorsal or ventral muscle contraction (Wallen et al, 1985) as well as centralised embryonic Engrailed expression are already present (Hammond et al, 2009;Matsuura et al, 2008). In crown group gnathostomes, epaxial-hypaxial muscle segregation and innervation is well established (reviewed in (Fetcho, 1987).…”
Section: A Possible Scenario For the Evolution Of Vertebrate 3d-mobilitymentioning
confidence: 99%
“…7. Gene expressions of cyclostome are based both on lamprey and hagfish data (Engrailed: Matsuura et al 2008;Pax3/7: MaCauley andBronner-Fraser 2002, Kusakabe et al 2010;MRF-A: Kusakabe et al 2010;Pax1/9: Ota et al 2011;Bapx: Cerny et al 2010;PitxA: Boorman andShimeld 2002a, Uchida et al 2003;Tbx1/10: Sauka-Spengler et al 2002, andTiecke et al 2007). Embryonic expression of orthologous genes in the mesodermal components are compared between amphioxus, cyclostomes, S. torazame, and amniotes.…”
Section: Reinterpretation Of Mesodermal Segments In Basal Lineages-frmentioning
confidence: 99%